Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
We conclude that the point (-3, 0) does NOT satisfy the inequality.
Step-by-step explanation:
Given the expression
[tex]y\ge \:\left|x\right|+3\:\:\:\:[/tex]
putting x = -3 and y = 6
[tex]6\ge \left|-3\right|+3\:\:\:[/tex]
Apply absolute rule: |-a| = a
[tex]6\ge \:6[/tex]
TRUE
Thus, the point (-3, 6) satisfies the inequality.
Given the expression
[tex]y\ge \:\left|x\right|+3\:\:\:\:[/tex]
putting x = 0 and y = 4
[tex]4\ge \left|0\right|+3[/tex]
Apply absolute rule: |a| = a, a≥0
[tex]4\ge \:3[/tex]
TRUE
Thus, the point (0, 4) satisfies the inequality.
Given the expression
[tex]y\ge \:\left|x\right|+3\:\:\:\:[/tex]
putting x = -3 and y = 0
[tex]0\ge \left|-3\right|+3\:\:\:[/tex]
Apply absolute rule: |-a| = a
[tex]0\ge \:6[/tex]
FALSE
Thus, the point (-3, 0) does NOT satisfy the inequality.
Therefore, we conclude that the point (-3, 0) does NOT satisfy the inequality.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.